Perception of Shopkeepers, Residents and Visitors on Mixed Land use in core area of Pune: Exploring the Impact of Mixed Land Use in Pune's Core Area (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Mixed land use typology is referred to the area where different types of land uses existtogether. It can include residential, commercial, administrative, industrial etc. Pune is a vastlydeveloping city. There have been great residential and commercial developments in Pune. An advantageof mixed-use development is the convenient walking access to living, work, and shopping. Though thereare many advantages to urban mixed-use living, there are many obstacles to mixed-use developments, aswell. There must be some problems regarding to the quality of life and may be some health issuesbecause of the mixed land use. At the same time, the convenience of the user of getting their dailyrequirement in nearby area increases the demand in the urban living. Mixed land use is important andleads towards benefits of urban development in city like Pune. The core area of Pune is very old andhistoric. It has combination of many old and modern type of building. Some of the old buildings are alsomixed used and make large difference in living environment for people. There must have been some prosand some cons for people who live in that development. It is important to understand how user of Punecity found this type of land in beneficial or in non-beneficial way.